Smartphones and equal access for people who are blind or have low vision - Locke, K.; Ellis, Katie; Kent, Mike; McRae, L.; Peaty, Gwyneth (2020)
This report explores the way Vision Australia clients are using smartphone technology in their everyday lives. It details findings of the research project, Smartphones and equal access for people who are blind or have low vision, conducted in collaboration with Vision Australia. The research centred on a survey conducted during February and March 2020 that aimed to explore the usage patterns and experience of using a smartphone for people with low vision or blindness. It aimed to discover how important the smartphone is for this cohort, what they use their device for, what limitations or obstacles they face, and what might make the smartphone more useful and accessible for them.